Efectividad de la educación en el conocimiento materno sobre cuidados del recién nacido en madres primíparas - Paz Salinas, Cinthia Lucia Rodríguez Mendoza, Alessandra (2022)
This research is quantitative, cross-sectional, pre-experimental with a pre-test and post-test design, entitled "Effectiveness of education in maternal knowledge about newborn care in primiparous mothers". Its objective was to determine the level of maternal knowledge in newborn care by primiparous mothers in the Alto Trujillo Health Center. The sample consisted of 40 primiparous mothers who had a newborn under 28 days who were cared for in the CRED service, to whom a questionnaire on the level of maternal knowledge about newborn care was applied. The information collected through the instruments was entered and processed through a virtual platform. Before the application of the education, it was evidenced that 57.5 percent of the primiparous mothers presented a medium level of knowledge about the care of the newborn, 37.5 percent a high level and finally 5.0 percent obtained a low knowledge. After the application of education, it was found that 100 percent of the mothers had a high level of knowledge. For the statistical analysis, the non-parametric Wilcoxon test was used, obtaining a significance less than or equal to 0.05 (p=0.000≤0.05), concluding that education was effective in increasing the level of knowledge of first-time mothers about the care of the newborn. born.